Multi-Level Gas Monitoring: A New Approach in Earthquake Research - Woith, Heiko; Daskalopoulou, Kyriaki; Zimmer, Martin; Fischer, Tomáš; Vlček, Josef; Trubač, Jakub; Rosberg, Jan-Erik; Vylita, Tomáš; Dahm, Torsten (Frontiers in Earth Science, 2020)
Fluid anomalies were often considered as possible precursors before earthquakes. However, fluid properties at the surface can change for a variety of reasons, including environmental changes near the surface, the response of the superficial fluid system to loads associated with the mechanical nucleation of earthquake fractures, or as a result of transients in fluid flow from the depths. A key problem is to understand the origin of the anomaly and to distinguish between different causes. We present a new approach to monitor geochemical and geophysical fluid properties along a vertical profile in a set of drillings from a depth of a few hundred metres to the surface. This setup can provide hints on the origin of temporal variations, as the migration direction and speed of properties can be measured. In addition, potential admixtures of fluids from a deep crustal or mantle origin with meteoric fluids can be better quantified. A prototype of a multi-level gas monitoring system comprising flow and pressure probes, as well as monitoring of fluid-geochemical properties and stable isotopes is being implemented in a mofette field with massive CO2 (up to 97 tons per day) degassing. The mofette is believed a gas emission site where CO2 ascends through crustal-scale conduits from as deep as the upper mantle, and may therefore provide a natural window to ongoing magmatic processes at mantle depth. Fluids from three adjacent boreholes - 30 m, 70 m, and 230 m deep - will be continuously monitored at high sampling rates.